The need for a European hepatitis C programme monitoring resistance to direct-acting antiviral agents in real life to eliminate hepatitis C - Stephanie Popping; Valeria Cento; Federico García; Francesca Ceccherini-Silberstein; Carole Seguin-Devaux; David A.M.C. Vijver, van de; Charles A. Boucher (Elsevier, 2018)
The World Health Organization (WHO) has declared that hepatitis C virus (HCV) should be eliminated as a public health threat. A key recommendation to reach this elimination goal, is to reduce new infections by 90% and liver-related mortality by 65%. Highly effective direct-acting antiviral agents (DAA) play a major role in this elimination. Unfortunately, DAA treatment fails approximately 2.5-5% of patients, often in the presence of resistance-associated substitutions (RAS). This could eventually lead to a total number of 1.8-3.6 million first-line DAA failures. RAS may jeopardise the elimination goals for several reasons; most importantly, virus transmission and infection progression will continue. More data are required to handle RAS adequately and identify mutational patterns causing resistance. Currently, sample sizes are small, data are scattered and methods heterogenic. Collaboration is therefore key and a European collaboration, such as HEPCARE, should provide a solution.